Carcass records of autumn-slaughtered reindeer as indicator of long-term changes in animal condition - Olofsson, Anna; Danell, Öje; Åhman, Birgitta; Forslund, Pär (Rangifer, 2011)
This study investigates the possibility of using carcass records from the commercial slaughter of reindeer as indicator of long-term changes in animal condition and, thus, the condition and use of their snow-free pasture. The aim was to assess the suitability of this indicator for use within adaptive management programmes for reindeer husbandry grazing resources. Data comprising measurements of carcass weight, conformation and fatness taken from commercial reindeer slaughter between 1994 and 2007, were analysed in relation to year, slaughter date, herding district, population density, and three categories of animals selected for slaughter. The carcass measures were significantly affected by year, and the effects were strongly correlated among the three animal categories. There were generally positive trends over the 14-year period studied. We identified several factors that should be considered when using carcass data to indicate long-term changes in animal body condition: (i) slaughter date had different effects depending on animal category; (ii) reindeer population density negatively affected female and calf carcasses, but not male carcasses. The effects of herding district were similar for carcasses of calves and females, but differed between females and males. Some of the differences between animal categories may be due to differing timing of slaughter (point i above), by different slaughter selection among districts, or have ecological explanations, e.g. sex differences in range use. Uncertainties in the classification of animals when using skeletal development to discriminate between calf and yearling carcasses, may also add to differences among districts. That population density effects on body condition were detectable together with the similarities in the effects of year and general long-term trends between animal categories support the suggestion that carcass measures can be used to indicate general changes in reindeer body condition and range use.